Analysis of the Financial Statements of PT Japfa Comfeed Indonesia Tbk (JPFA) for the Financial Year 2023 and Comparison with its Main Competitor PT Charoen Pokphan Indonesia TBK (CPIN) - Yanuar Ramadhan; Shadiqy Artib; Novia Dewi Siti Nurhaliza; Yakub Gunawan; Yusnaini Yusnaini (Eduvest - Journal of Universal Studies, 2025)
Analysis of the 2023 financial statements compared to the 2022 financial statements and financial statements of major competitors is important to understand the company's performance and prospects. Objectives This study aims to analyze the financial statements of Japfa Comfeed Indonesia for the financial year 2023 in comparison with the financial year 2022 and compared with the main competitor, PT Charoen Pokphan Indonesia, using financial ratios. This study uses secondary data derived from the financial statements of Japfa Confeed Indonesia in 2022, 2023 and the financial statements of PT Charoen Pokphan Indonesia in 2023. The results showed that the financial ratio analysis of PT Japfa Comfeed Indonesia (JPFA) in 2023 showed a decrease in liquidity compared to 2022, although it was still sufficient for short-term obligations and better than CPIN. Activity ratios stagnated, while leverage increased with a higher debt burden than CPIN. JPFA's profitability also declined, with no dividend distribution, in contrast to CPIN which paid dividends. These results reflect JPFA's financial challenges amid competition with CPIN in the same year. From this research it can be concluded that PT Japfa Comfeed Indonesia's finances in 2023 are still quite good and able to fulfill short-term obligations, but when compared to its main competitor, in 2023 it appears that PT Charoen Pokphan Indonesia is better performing.